Doxa and local elite habitus in the symbolic-based power struggle arena in Tidore - Wahid, Bustamin; Ishomuddin, Ishomuddin; Winarjo, Wahyudi; Kartono, Rinikso (Technium Social Sciences Journal, 2021)
This article describes a socio-political phenomenon that occurred in Tidore community during the momentum of Local Leaders Election (pilkada). Political phenomena do not only involve rational instruments, but also cultural and supernatural/mystical/occult dimensions being part of a mechanism for power struggle. Values, norms, and traditional leaders (nature and shari'a) are involved in a political contestation. The phenomenon of jinn and mystical/occult power is part of the capital to produce power in Tidore or in another sense; symbolic capital becomes a political mobilization strategy in Tidore. The aims of this research are (1) to analyze power and describe the process of doxa formation and elite habitus/political actors in the symbolic- based power struggle arena in Tidore. (2) to analyze and describe the strategies of the local elite in using symbolic capital in the arena of power struggle in Tidore (Local Leaders Election). This research uses qualitative method with ethnographic research. The research subjects are the indigenous people of Gurabunga, the political elite/political actors, Sowohi, the Sultan and people who are involved and understand the Local Leaders Election (pilkada). Data collection was done by interview, observation and documentation study. The researchers conduct an in-depth study so that the data can be maximal and adequate, and triangulation is carried out. Then this data was analyzed using an ethnographic approach. The theory used as an analytical tool in this research is Perre Bourdieu's Theory of Doxa, Habitus and Arena. The results of the study prove that the process of forming doxa and political habitus has a strong influence on the political practice of the Tidore people. Values, norms, customs and local beliefs of the community have an effect on the dynamics and political reality in Tidore. And symbolic capital as the most important part in producing power in Tidore Keywords: Doxa, Habitus, Symbolic-based Power Struggle